PENGARUH PIJAT PUNGGUNG TERHADAP PENURUNAN NYERI PERSALINAN: EVIDENCE BASED CASE REPORT (Jurnal Kesehatan Siliwangi, 2023)
Background: Childbirth is a process that cannot be separated from the pain that every woman will experience. Pain is a condition where a person feels uncomfortable on a varying scale and only that person can describe the condition of the pain she feels. Back massage or compression of the sacrum bones is one way to reduce pain during labor. In theory, back massage is very good to do just before labor, by rubbing the back, it is very effective in reducing pain during labor. The pain control effect on back massage therapy only lasts as long as the massage is being performed. Purpose: The purpose of this case study is to apply back massage to reduce pain in the first stage of labor. Methode: The method used is a way of searching for evidence through databases from PubMed and Cochrane with the year of publication 2012 – 2022. Result: The results of the case report study show that back massage reduces labor pain in mothers who experience pain. Conclusion: Back massage reduces labor pain in women giving birth.